CORONAVIRUS DISEASE 2019 VACCINATION DRIVE: THE PERCEPTIONS AND ACCEPTANCE OF VACCINATION AMONG HEALTH CARE WORKERS - VISWANATH, KASI; RN, HIREMATH; BASRA, SHARANJIT SINGH; CHOUREY, NIRAJ; KUMAR, DOBI SRAVAN (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: Coronavirus disease 2019 (COVID-19) infection evolved as a worst nightmare across entire humanity especially for health care workers along with all stakeholders of the society ever since the beginning of year 2020. Vaccination campaign is one of the most successful public health interventions and a cornerstone for the prevention of communicable infectious diseases. To have a baseline data and to form the basis for further vaccination drive, we carried out this study with an objective to understand the perception and COVID-19 vaccine hesitancy among health care workers (HCWs). Methods: A correctional study was carried out at one of the multispecialty hospital in North India where COVID-19 vaccination for HCWs was planned and 675 HCWs were taken into the study. Data were collected by means of personal interview using pretested semi-structured questionnaire and Epi Info version 6 was used for analysis. Results: The mean age of the participants was 32.78 years. Majority were male (89.48%), working in government sector (87.7%) and paramedic (88.15%). While 94.67% were accepting vaccine voluntarily while remaining were not confident enough on their own, only 26.96% were ready to take vaccine even on payment. The overall awareness scores of study participants were calculated and found that 79.56% of them had poor awareness level while only 20.44% had satisfactory awareness level. The association of awareness score was statistically significant with job profile (designation), gender, and prior COVID-19 positivity of study participants. Conclusion: The decision of vaccine prioritization to HCWs and frontline workers will boost the morale and spirit of warriors high in future. This study was a preliminary attempt to check any vaccine hesitancy factors among HCWs and act accordingly. Although almost all had volunteered for vaccine, the knowledge about vaccine was poor in majority of HCWs as the time period was recent to vaccine rollout and detailed research findings were not yet out about vaccine. All measures to be taken including intensive information education and communications activities targeting HCWs and general population on regular basis to upgrade the knowledge on vaccine issues. A strong communicating policy in an era of misinformation is highly recommended as social media plays an important role in spreading true as well as false messages jeopardizing the entire gains of successful vaccination and attainment of herd immunity. HCWs to act as role model for general public and patients which would in turn increase the vaccine acceptance among them.